2017
DOI: 10.1007/s12094-017-1788-x
|View full text |Cite
|
Sign up to set email alerts
|

LOC285629 regulates cell proliferation and motility in colorectal cancer cells

Abstract: Our findings suggest that LOC285629 may be further developed as a potential therapeutic target for CRC treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
2
0
1
Order By: Relevance
“…Moreover, ENO2 was found to be significantly upregulated in a metastatic colon cancer cell line, which indicated a likely correlation with the metastatic mechanism in vitro and in vivo [ 28 ]. Some studies showed that a lncRNA (LOC285629) is involved in CRC pathogenesis through direct or indirect association with ENO2 [ 29 ]. Other research indicated that ENO2 combined with other known CRC markers can distinguish early-phase malignant colorectal tumors from benign tumors [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, ENO2 was found to be significantly upregulated in a metastatic colon cancer cell line, which indicated a likely correlation with the metastatic mechanism in vitro and in vivo [ 28 ]. Some studies showed that a lncRNA (LOC285629) is involved in CRC pathogenesis through direct or indirect association with ENO2 [ 29 ]. Other research indicated that ENO2 combined with other known CRC markers can distinguish early-phase malignant colorectal tumors from benign tumors [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…本研究通过对TCGA数据库样本的整理和铜死亡相关lncRNA的筛选,利用多因素Cox回归分析共获得9个与膀胱癌患者预后相关的铜死亡相关lncRNA,其中 AC105001.1 、 AC103746.1 、 AL031651.2 和 LINC02159 为膀胱癌患者预后的危险因素, AC108516.2 、 AC007993.3 、 LINC01648 、 AC006160.1 和 SCAMP1 - AS1 为保护因素。有研究显示,在发生心肌梗死的患者中, AC103746.1 在血管生成中具有重要的促进作用 [ 20 ] 。膀胱癌是公认的具有高度血管化的肿瘤,血管密度作为膀胱癌患者预后的独立指标,同时高血管密度也是癌症复发的危险因素 [ 21 - 22 ] 。本文资料提示 AC103746.1 是膀胱癌患者预后的不良因素,推测可能是通过影响血管形成从而促进膀胱癌的进展。 LINC02159 ,又名 LOC285629 ,为食管鳞癌的低风险基因之一 [ 23 ] ,可能通过降低PGRN、PDGF-AA、烯醇化酶2和p70核糖体蛋白S6激酶等表达从而阻碍结直肠癌进展,并且可能降低癌症的耐药性,其表达水平与结直肠癌预后显著相关 [ 24 ] 。但膀胱癌中PGRN/EphA2轴可能会促进血管形成,有助于膀胱癌的进展 [ 25 ] 。因此, LINC02159 可能通过靶向PGRN促进膀胱癌的发生和发展。在保护因素方面,有研究显示 AC006160.1 过表达可显著抑制膀胱癌细胞株的增殖和侵袭能力,可作为膀胱癌发展的保护因素 [ 26 ] ,本研究结果与之相符。在肺腺癌患者中, SCAMP1 - AS1 在N2期中的表达低于N0分期和N1分期 [ 27 ] ,表明 SCAMP1 - AS1 可能在肺腺癌中抑制肿瘤进展,本文资料显示 SCAMP1 - AS1 在膀胱癌中同样扮演阻碍其发生和进展的角色。除上述4个lncRNA外,有文献报道 LINC01648 与糖化血红蛋白相关 [ 28 ] ,其余4个lncRNA的功能则尚未见文献报道,需要进一步研究。…”
Section: 讨论unclassified
“…Tumor and non-tumor tissue samples were obtained from CRC patients during surgical resection of the tumor. A subset of tissues from these patients was previously used to detect a specific long non-coding RNA in a different study [21] . Demographic data of the patients is shown in Table 1.…”
Section: Collection Of the Tissue Specimensmentioning
confidence: 99%